Association between neurological injury and the severity of oropharyngeal dysphagia after stroke - Danielle Martins Otto; Marlise de Castro Ribeiro; Liselotte Menke Barea; Renata Mancopes; Sheila Tamanini de Almeida (CoDAS, 2016)
ABSTRACT Purpose To associate the degree of biomechanical impairment in the swallowing process with the severity (National Institute of Health Stroke Scale – NIHSS) and type of neurological injury in patients post stroke. Methods A cross-sectional, descriptive study conducted with 42 patients (22 females), aged 65.7 years on average diagnosed with stroke. All patients underwent clinical neurological evaluation and application of the NIHSS in the first 48 hours after stroke. The swallowing function was evaluated using the Functional Oral Intake Scale (FOIS) and the Protocol for the Investigation of Oropharyngeal Dysphagia in Adults. The Fisher’s Exact Probability Test was used to assess the correlation between the degree of swallowing impairment and the severity (NIHSS score) and type of stroke. The study results were statistically analyzed at 5% significance level (p≤0.05). Results 92.9% of the patients presented ischemic stroke; 59.5% presented impairment of the anterior cerebral circulation. Statistically significant correlation was found between the neurological scale (NIHSS) scores and the swallowing impairment scale (p=0.016). Conclusion An association between stroke severity and oropharyngeal dysphagia severity was observed. A high proportion of patients with ischemic stroke with circulation affected in the anterior cerebral region presented severe oropharyngeal dysphagia. No statistically significant correlation was observed between the FOIS scale and stroke severity.